Urban entrepreneurs in port revitalization projects in Rio de Janeiro - Riscado, Júlia Erminia (Pontifícia Universidade Católica de São Paulo, 2020)
This article aims to analyze the performance of urban entrepreneurs in the Rio de Janeiro port area up to the implementation of the Porto Maravilha Project. Initially, the article addresses the theoretical references that guide studies about the place of interest groups in the process of formulating agendas, highlighting the role of political entrepreneurs. The second part of the article provides a historical recovery of the revitalization projects for the port region since the 1980s. Based on this, it was possible to observe the participation of certain business groups and public agents in the development of the projects. Our intention was to identify their relevant role in the management and in the making of urban policies in the city of Rio de Janeiro.